2022
DOI: 10.3390/molecules27207106
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Biological Activities of the Lotus Root Polysaccharide-Iron (III) Complex

Abstract: In this study, the synthesis parameters of the lotus root polysaccharide iron complex (LRPF) were determined and optimized by response surface methodology. Under the optimum preparation conditions, the pH of the solution was 9, the ratio of M (trisodium citrate): m (lotus root polysaccharide) was 0.45, the reaction time was 3 h. UV spectroscopy, thermogravimetry, FT-IR spectroscopy, X-ray diffraction, CD, and NMR were used for the characterization of the LRPF. LRPF has good stability and easily releases iron i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The absorption peak of the PCP1C-iron (III) complex at 850 cm −1 indicated that the iron in PCP1C-iron (III) complex existed in the form of the β-FeOOH iron core [ 22 ]. The carbonyl absorption peak at 1666 cm −1 indicated that Fe (III) complexes with carbonyl caused a change in carbonyl vibration dipole moment [ 5 ]. The absorption peak at 3413 cm −1 was the vibration absorption peak of the hydroxyl group in the polysaccharide molecule [ 32 ], and the absorption peak was narrowed after complexing with Fe (III), indicating that the hydroxyl group in the polysaccharide participated in the complexation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption peak of the PCP1C-iron (III) complex at 850 cm −1 indicated that the iron in PCP1C-iron (III) complex existed in the form of the β-FeOOH iron core [ 22 ]. The carbonyl absorption peak at 1666 cm −1 indicated that Fe (III) complexes with carbonyl caused a change in carbonyl vibration dipole moment [ 5 ]. The absorption peak at 3413 cm −1 was the vibration absorption peak of the hydroxyl group in the polysaccharide molecule [ 32 ], and the absorption peak was narrowed after complexing with Fe (III), indicating that the hydroxyl group in the polysaccharide participated in the complexation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, polysaccharide iron represented by Niferex has attracted considerable attention because of its stable structure, high bioavailability, and high iron content [ 4 ]. In addition, polysaccharide iron not only has the activity of supplementing iron, but also has other beneficial activities of polysaccharide [ 5 8 ]. Although polysaccharide iron has been recognized as a potential drug to treat IDA, the clinical application of polysaccharide iron prepared from plant polysaccharides is limited at present, which may be related to the unclear activity of polysaccharide iron and the low purity of polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the sweet corn cob polysaccharide-iron (III) complex is more thermally stable. Moreover, introducing iron (III) binding to −OOH and −OH in polysaccharides leads to a more stable β-FeOOH iron core [ 28 ]. Therefore, it can significantly improve the stability of the complex compared to that of SCCP.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, an evaluation about the effects of the supplementation of dietary CYP-Cu on serum antioxidative parameters of broilers demonstrated that dietary CYP-Cu significantly increased the serum concentrations of T-SOD, T-AOC, GSH-ST, GSH-Px, and decreased the serum concentrations of MDA of broilers (0.10 g/kg CYP-Cu group), which revealed that CYP-Cu had strong antioxidant activity. A previous study shown that lotus root polysaccharide iron complex could significantly increase the antioxidant capacity of mice by increasing the serum levels of CAT, SOD, and GSH-Px ( 31 ), and showed a trend of first increasing from 2 to 8 mg/mL and then decreasing. Similarly, Dong et al ( 32 ) found that Flammulina velutipes polysacchrides and polysacchride-iron (III) complex inhibited the MDA production of health mice liver and improve its antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%